Gender differences in the workplace: the case of pharmaceutical industry in China - Silva, M. G.; Zhao, F. (European Academy of Management Conference, EURAM 2019, 2019)
Gender’s equality is still an allusive phenomenon in twenty-first century workplaces. Previous studies have suggested that gendered assumptions and organizational factors may contribute to gender’s inequality. However, little research has investigated how individuals make sense of their roles in the workplace in the Chinese context. Drawing on cultural constructions of gender’s roles in organizations, we address three research questions: What are the meanings different actors ascribed to the sales occupation? To what extent are different actors able to (re)construct the dominant culture in the sales context? What are the implications of existing reproduction processes of the dominant culture for the way people experience their lives at the workplace? Through a discourse analysis this article examines the transcripts of thirty narratives on women in sale roles to critically analyse people attitudes to transform the dominant culture in working life. We argue that initiatives sponsored at different organizational ladders, and by both genders, are (un)consciously reproducing sales occupation’s masculine cultures in the pharmaceutical sales industry. The study reveals that while there is a discursive space within the salesforce for gender’s equality, in practice men and women at the workplace engage in masculine status quo, contributing to legitimize unequal relations between the genders in the sales industry in China.